Awareness KAP on Covid-19 Among University Students in Sabah - Nur Shahida Ab Fatah; Nurhasim Muhammad Fikri; Kaltes Isyraf Amin; Jaafar, A.S.I.A.; Amran, I.; Aslina Baharum (Accent Social and Welfare Society, 2021)
Many countries have taken the initiative to lockdown their country to control the Coronavirus disease 2019 (COVID-19) outbreak. The knowledge, attitudes and practice (KAP) on COVID-19 plays a vital role to decide whether this lockdown movement was effective. A total of 37 students participated in a survey to see how far the student's awareness about KAP towards COVID-19 was conducted online between July, 7th until 12th, 2020. The questionnaire included demographic characteristics consist of eighteen items knowledge A, eight items knowledge B, fifteen items on attitude and twelve items on practices. Data collection conducted using the quantitative method from the online survey. The results indicate that students in Sabah have strong knowledge of COVID-19 and a manageable solution to resolving the pandemic.